Notices of the Castle and Painted Room or Hall of Earlshall, in Fifeshire - Jervise, Andrew (Proceedings of the Society of Antiquaries of Scotland, 1863)
The article briefly discusses the history of the Bruce family that owned Earlshall Castle and which family members contributed to its construction. The author highlights the painted ceiling in the hall as a particularly interesting part of the architecture. He provides lists of the paintings’ subjects and describes some of the families and individuals referenced in the artwork.